Exploring the influence of conserved lysine69 on the catalytic activity of the helicobacter pylori shikimate dehydrogenase: A combined QM/MM and MD simulations. (December 2019) - Li, Jun; Wu, Ge'an; Fu, Qiang; Ge, Heng'an; Liu, Shu; Li, Xiaolong; Cheng, Biao
Highlights: Revealing the role of Lys69 in the catalytic activity of SDH at the atomic level. Lys69 maintains the stability of substrate shikimate in the active site. This work can advance our understanding the catalytic mechanism of SDH family. Abstract: Shikimate dehydrogenase (SDH) catalyzes the reversible, NADPH-dependent reduction of 3-dehydroshikimate to shikimate, involved in the shikimate pathway. This pathway has emerged as an important target for the development of antimicrobial agent. Structural and functional analyses suggest that the conserved Lys69 plays an important role in the catalytic activity of Helicobacter pylori ( H. pylori ) SDH. However, the detailed mechanism how mutation of Lys69 affects the catalytic activity of H. pylori SDH remains unclear. Here, two-layered ONIOM-based quantum mechanics/molecular mechanics (QM/MM) calculation and molecular dynamics (MD) simulations were performed to explore the role of Lys69 in the H. pylori SDH. Our results showed that in addition to act as a catalytic base, the conserved Lys69 plays an additional, important role in the maintenance of the substrate shikimate in the active site, facilitating the catalytic reaction between the cofactor NADP + and shikimate. Mutation of Lys69 triggers the movement of shikimate away from the active site of SDH, thereby disrupting the catalytic activity. This result can advance our understanding the catalytic mechanism of SDH family, which may benefit of the rational design of SDH inhibitors.